Pengaruh kualitas produk, desain dan harga terhadap keputusan pembelian konsumen Andreas Menswear - Hertina, Dede; Apriansyah, Alifa; Wirawan, Ari (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this study was to determine the effect of product quality, design, and price on consumer purchasing decisions at the Andreas Menswear company. This study uses the associative method to determine the relationship between one variable and another. Data were taken using a questionnaire, through validity testing, reliability testing, multiple regression analysis test, and hypothesis testing through t test. The results showed that product quality, design, and price had an effect on consumer purchasing decisions for Andreas Menswear.